Renewable technologies in Karnataka, India: jobs potential and co-benefits. (7th February 2019) - Kattumuri, Ruth; Kruse, Tobias
Abstract : The tangible benefits of renewable energy technologies are a crucial parameter when determining the political feasibility of adopting a low-carbon development path, particularly for emerging economies. We present that these potential benefits consist of 'green jobs' and of a wider set of socio-economic and environmental 'co-benefits' that are generated simultaneously from renewable technologies in India. Based on case studies from the Indian state of Karnataka, we obtain estimates for jobs and describe co-benefits enabled by wind, off-grid solar and biomass technologies. Furthermore, we use these estimates to project the potential for future benefits that could be generated by further enhancing the use of renewable technologies towards sustainable energy policy and security. We show that enhancing green economy offers benefits that include the creation of jobs, but also delivers a much wider set of socio-economic and environmental welfare gains for emerging economies such as India. Our paper also provides valuable evidence-based analyses for policy-makers when assessing the benefits of low-carbon sustainable development.